A healthy decline in age- and sex- specific incidence of hip fractures in the elderly in the Republic of Ireland. Issue 5 (October 2020) - Coveney, Eamonn I.; McKeown, Declan; Quinlan, John F.; Cleary, May
Abstract: Aim: The number of patients sustaining hip fractures in the Republic of Ireland was expected to increase by 100% from 2004 to 2026. This has not been seen either in local or international literature. Our aim is to assess the age- and sex-specific incidence of hip fractures in patients over the age of 65 years and to determine whether the projected increase in incidence is mirrored in the reality of the Irish experience. Methods: This is a retrospective observational cohort study including all patients with a hip fracture from a tertiary referral centre from 2005 to 2015. Population data was obtained from the Central Statistics Office of Ireland. Results: 3818 hip fractures in the over 65 age group were recorded. The highest incidence of hip fractures occurred in the 85–90 year old age group. For all ages over 65, the incidence of hip fractures in females over the 10 year period is significantly reducing (p < 0.01). There were 955 hip fractures per 100, 000 in females in 2010 and 410 per 100, 000 in males. In 2014, this had reduced to 668 in females and 332 in males respectively. Conclusion: The annual hip fracture incidence has decreased across both sexes in this study period. This may be associated with preventative measures and introduction of fracture liaison services. This study highlights the importance of investment in preventative strategies for a continued reduction in hip fracture incidence and will help to plan future services.